Investigation of High-Temperature Durability and Microstructure Evolution of G115 Steel After Long-Term Aging at 650 °C - Shaohai Ma; Shun Han; Xinyang Li; Yong Li; Chunxu Wang (Metals)
This study investigated the high-temperature tensile durability of G115 steel after aging at 650 °C for different periods of time using a high-temperature tensile testing system. The results show that with the increase in aging time, the microstructure of G115 steel changes to a certain extent, which shows that as the martensite lath width and HAGB increases, the dislocation density decreases and the second precipitate shows obvious growth. As the tensile test temperature increases, the tensile strength decreases from ~750 MPa to ~350 MPa. The effect of aging time on the high-temperature tensile durability of steel after a 3000 h aging process is not significant, which should be related to the relatively high microstructure thermal stability of G115 steel during the aging process.